Investigating the Relationship Between Immunohistochemical Expression of CA 125 in Ovarian Epithelial Tumors and Serum Levels as Diagnostic Indicators - Fianda Restalia; Dwi Andhika Panjarwanto; Johannes Sudarwantono; Daniel Alexander Suseno; I Wayan Agung Indrawan (Pusat Publikasi Nusantara, 2025)
This systematic literature review evaluates the relationship between CA-125 immunohistochemical expression in ovarian epithelial tumors and serum CA-125 levels as diagnostic indicators. Five studies meeting inclusion criteria from 20,500 initially identified articles consistently demonstrated significant positive correlations between tissue expression intensity and serum concentrations. Key findings reveal that elevated preoperative serum levels correspond directly with increased tissue expression intensity, while combined assessment improves diagnostic accuracy. Both parameters effectively predict early recurrence in advanced-stage (III/IV) disease and show distinct variation across histological subtypes, with mucinous carcinomas exhibiting the lowest expression levels. However, methodological limitations, including heterogeneous study designs, varying immunohistochemical techniques, and restricted sample sizes, affect generalizability. Clinical implications support integrating tissue immunohistochemistry with serum measurements and complementary biomarkers like HE4 for enhanced subtype differentiation. Future multicenter prospective studies with standardized protocols are recommended to establish definitive cut-off values and long-term prognostic significance. These findings underscore CA-125’s enduring clinical value while emphasizing that optimal diagnostic performance requires contextual interpretation alongside other markers, histological classification, and comprehensive patient assessment. The systematic PRISMA-guided approach ensured rigorous evidence synthesis, highlighting CA-125’s crucial role in addressing ovarian cancer’s significant global burden through improved early detection strategies.